Kutemukan Kebenaran: Psikologi Spiritual dan Motivasi Beragama Mualaf Dewasa - Khoiri, Athiful (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2021)
Abstract. This research aims to obtain the dynamics of religious motivation in converts, it is seen from the factors that influence it, this research uses qualitative research methods with phenomenology study approach and collect related data from several techniques, such as interviews and observation. The study participants consisted of three adult muallafs/convert living in Sleman regency. The results of the study show that the religious motivation of converts is intrinsic, which is more motivated by the individual’s self, and external encouragement, namely child and family factors. Religiuos motivation is also shown by the factors of religiuos motivation experienced by converts, including their attitude when they first converted to Islam, confront existing obtacles with a firm and strong commitment, and maintaining the belief in the truth of Islam by practicing Islamic law well in daily life.